A compact algorithm for semi-analytical computing of internal forces in RC cross-section - Matuszak, Aleksander; Pluciński, Piotr (AIP conference proceedings, 2018)
Integration of stress in an RC cross-section is an important step in any computation of an RC beam or frame. In a standard procedure, the numerical integration is used in most cases. However, in 2005, Zupan & Saje developed a semi-analytical method of section stress integration [1]. This paper discusses a compact algorithm for the method published by Zupan & Saje. The compactness is achieved by splitting the computations into two parts: the first one focuses on calculating stress integrals which are independent of the section geometry and the second on generating coefficients dependent on the geometry but not on stress. In order to demonstrate the steps of the algorithm, the authors have provided a detailed example of the most frequently studied section, published by Fafitis [2]. The complete algorithm is presented in the last part of the paper.